Efektivitas Pendekatan CTL Dan Discovery Terhadap Kemampuan Berpikir Kreatif Dalam Pemecahan Masalah Mahasiswa PGSD UMKO - Berta Aprisa; Yasint Mahendra (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This study compares the effects of the contextual teaching and learning (CTL) approach and the discovery approach, the name by providing problem-solving problems in mathematics learning on the creative thinking abilities of PGSD students at Muhammadiyah University, Kotabumi. This type of research is a quasi-experimental research with a pretest and posttest nonequivalent group design. The subjects in this study were students of class A and class B PGSD, Muhammadiyah University, Kotabumi, 2019/2020 academic year. Instruments / measuring instruments in this study are in the form of questions that require problem-solving, the questions given have also been validated by mathematicians as a reference for measuring students' creative thinking abilities. In the next stage, the data that has been obtained by the researcher is analyzed using descriptive analysis test, inferential analysis test which includes the normality test, homogeneity, and Hotelling's test. From the results of the requirements test that are normally distributed and homogeneous, a significance level of 5% is obtained, this indicates that the contextual teaching and learning (CTL) approach and the discovery approach are equally effective as methods of learning mathematics for UMKO PGSD Students to improve creative thinking skills. Students who are use to solve mathematics problems.